2017
DOI: 10.1287/isre.2017.0694
|View full text |Cite
|
Sign up to set email alerts
|

Disconfirmation Effect on Online Rating Behavior: A Structural Model

Abstract: This research studies the effect of disconfirmation—the discrepancy between the expected and experienced assessment of the same product—on the behavior of consumers leaving online product reviews. We propose a modeling framework in which an individual’s prepurchase expectation is shaped by (1) the product ratings she observes and (2) the perception of the review system she has at the time of the purchase. Upon product consumption, the individual obtains the postpurchase evaluation and encounters a certain leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
102
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 158 publications
(104 citation statements)
references
References 30 publications
2
102
0
Order By: Relevance
“…Regarding individual experience, research has shown that customers with extreme opinions will be more likely to contribute online reviews (Dellarocas and Narayan 2006). Prior research has also suggested that disconfirmation of expectations, which are formed on top of previous reviews, may increase customers' motivation to write a review (Ho et al 2017). Moreover, the social influence from the community may affect the review motivation.…”
Section: Drivers Of Online Reviewsmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding individual experience, research has shown that customers with extreme opinions will be more likely to contribute online reviews (Dellarocas and Narayan 2006). Prior research has also suggested that disconfirmation of expectations, which are formed on top of previous reviews, may increase customers' motivation to write a review (Ho et al 2017). Moreover, the social influence from the community may affect the review motivation.…”
Section: Drivers Of Online Reviewsmentioning
confidence: 99%
“…An alternative mechanism is that MRs may affect future reviews through its impact on sales. Because MRs may highlight positive reviews and mitigate the impact of negative reviews, they may increase future sales given that consumers rely on reviews to evaluate products before purchase (Ho et al 2017). Recent research shows that MRs may indeed increase sales (Kumar et al 2017, Xie et al 2014.…”
Section: Mechanisms Of Managerial Responsementioning
confidence: 99%
“…For a platform, online reviews cannot act as an effective means to improve the quality and revenue. The platform should establish other policies and rules (eg: punitive measures, reputation management) that strengthen the supervision and control of this kind of low-quality products [45][46][47][48]. It also needs other supervisory departments to enhance the sense of responsibilities for government and severely punish those who undertake illegal activities.…”
Section: Proposition 1 When the Value Satisfiesmentioning
confidence: 99%
“…Although more data on CS are currently available at a lower cost, they may include biased or irrelevant information, which makes the extraction of true CS value more difficult. Ho et al (2017) reveal that a product's online ratings may not neutrally reflect customers' post-purchase evaluation due to the disconfirmation effect. Therefore, it is also intriguing to explore how the accuracy of CS measurement can affect the incentive design decision.…”
mentioning
confidence: 97%